Encapsulation and on-demand release of functional materials from conductive nanofibers via electrical signals. Issue 1 (1st March 2022) - Chen, Yijun; Boyd, James G; Naraghi, Mohammad
Abstract: The goal of this research is to establish a highly compact on-demand release platform for functional materials where porous nanofibers serve as the host, heat-based release trigger and temperature controller for regulated release. The ability to store functional materials in fibers and release them on demand via external signals may open up new frontiers in areas such as smart textiles and autonomous composites. The host material was porous carbon nanofibers (CNFs), which encapsulated functional materials, protected by a thin polymeric coating to thermally regulate the release. This platform was used to store Gentian violet (GV), an antibacterial material, and release it with highly controllable rates in aqueous environment. The high porosity of the CNF yarns, both inter- and intra-fiber porosity, resulted in a mass loading of as high as ∼50 wt%. The active release was triggered via passing electrical signals through CNF yarn backbone, thereby heating the coating. The rate of release as a function of temperature was measured. It was concluded that the release mechanism is via thermally augmented and reversible diffusion rates of GV and water through the coating. By applying electric current, the diffusion coefficient of the coating was increased, and the release rate dramatically increased in a reversible fashion by as much as 39×.